1993
DOI: 10.1111/j.1432-1033.1993.tb19875.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an aminopeptidase A fromStaphylococcus chromogenesand its use for the synthesis of amino‐acid derivatives and dipeptides

Abstract: An aminopeptidase with original specificity was purified 3800-fold to homogeneity from a cellular extract of Staphylococcus chromogenes. The enzyme was specific for acidic amino acids (Asp and Glu) at the N-terminus of peptides and thus can be classified as an aminopeptidase A. However, its specificity was not restricted to acidic amino acids: a-hydroxy acids such as L-malic and L-lactic acids were also accepted in position P1. The enzyme had a broad specificity for the residue at position P' 1, accepting all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Some studies suggest the high enzyme activity and/or stability in aqueous glymes. Yoshpe-Besancon et al 322 observed that a 55% triglyme solution could shi the equilibrium of aminopeptidase A from amide bond hydrolysis to peptide bond formation, which allowed a selective a-amino protection of derivatives of many amino acids (except glycine and proline) by the malyl group. Rosell et al 323 found that 50% (v/v) aqueous solutions of diglyme (G2) or tetraglyme (G4) depressed the hydrolytic activity of penicillin acylase by roughly 65%, but boosted its synthetic activity by $4.8 times.…”
Section: (Co-)solvents For Biocatalysismentioning
confidence: 99%
“…Some studies suggest the high enzyme activity and/or stability in aqueous glymes. Yoshpe-Besancon et al 322 observed that a 55% triglyme solution could shi the equilibrium of aminopeptidase A from amide bond hydrolysis to peptide bond formation, which allowed a selective a-amino protection of derivatives of many amino acids (except glycine and proline) by the malyl group. Rosell et al 323 found that 50% (v/v) aqueous solutions of diglyme (G2) or tetraglyme (G4) depressed the hydrolytic activity of penicillin acylase by roughly 65%, but boosted its synthetic activity by $4.8 times.…”
Section: (Co-)solvents For Biocatalysismentioning
confidence: 99%
“…35 A few studies suggested the high enzyme activity and/or stability in aqueous glymes. 3639 Our group 40 found that long-chain glymes are highly compatible with immobilized Candida antarctica lipase B.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, deprotection is necessary to obtain a dipeptide. In contrast, aminopeptidase from Staphylococcus chromogenes was reported as useful for dipeptide synthesis in a one-step reaction (Yoshpe-Besancon et al 1993).…”
Section: Introductionmentioning
confidence: 97%